PENGARUH GAYA KEPEMIMPINAN, PENGAWASAN DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI PADA KANTOR KEPENDUDUKAN DAN CATATAN SIPIL KABUPATEN MAJENE - Sri Indira Hartawati (Pusat Riset dan Inovasi Nasional, 2022)
This study aims to determine the effect of leadership style on employee performance at the Majene Regency Population and Civil Registry Office, to determine the effect of supervision on employee performance at the Majene Regency Population and Civil Registry Office, to determine the effect of work discipline on employee performance at the Majene Regency Population and Civil Registry Office. and find out which variable is more dominant in influencing employee performance at the Office of Population and Civil Registry of Majene Regency. This study uses a quantitative approach with data analysis techniques using SPSS. The results showed that 1) Leadership Style had an effect on Employee Performance at the Department of Population and Civil Registry of Majene Regency, 2) Supervision had an effect on Employee Performance at the Department of Population and Civil Registry of Majene Regency, 3) Work Discipline had no effect on Employee Performance at the Department of Population and Civil Registration. Civil Registry of Majene Regency and 4) Leadership Style variable has more influence on Employee Performance at the Department of Population and Civil Registry of Majene Regency. Keywords: leadership, supervision, work discipline, employee performance